From the Precursor to the Active State: Monitoring Metamorphosis of Electrocatalysts During Water Oxidation by In Situ Spectroscopy. Issue 8 (23rd June 2017) - Hollmann, Dirk; Rockstroh, Nils; Grabow, Kathleen; Bentrup, Ursula; Rabeah, Jabor; Polyakov, Mykola; Surkus, Annette‐Enrica; Schuhmann, Wolfgang; Hoch, Sascha; Brückner, Angelika
Abstract: In situ Raman and in situ EPR spectroscopy in combination with electrochemistry have been used to investigate the behavior of mixed cobalt nickel and cobalt copper oxides in the oxygen evolution reaction (OER). All experiments were carried out in homemade electrochemical cells using 0.1 M KOH as the electrolyte. The OER activities vary depending on the annealing conditions of the catalyst precursors, also reflected by different behaviours during the in situ spectroscopic experiments. The different activity of the Co/Ni oxides is most likely related to the formation of either γ‐ or β‐NiO(OH), characterized by distinct features in the Raman spectra. Thus, a higher percentage of β‐NiO(OH) is present in the more active catalyst. A different behaviour of Co/Cu catalysts has been shown by in situ Raman spectroscopy too, but the active phase could not be identified because of missing spectral features. However, in situ EPR spectroscopy revealed the partial dissolution of Cu(II), suggesting the formation of a Co‐enriched oxide/hydroxide surface. Abstract : Combine and conquer : In situ Raman and in situ EPR spectroscopy in combination with electrochemistry have been applied to study the behaviour of mixed Co/Ni and Co/Cu oxides during the oxygen evolution reaction (OER). Depending on the annealing conditions of the catalyst precursors different OER activities were obtained as also reflected by different changes of distinct spectral features during the in situ experiments.